2016
DOI: 10.2147/jpr.s113258
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-reported pain sensitivity and pain after total knee arthroplasty: a prospective study of 71 patients 8 weeks after a standardized fast-track

Abstract: Background and purposeThis was a prospective cohort study assessing data from 71 adult patients undergoing total knee arthroplasty (TKA) following a standardized fast-track program between January and July 2013. The objective was to examine the relationship between self-rated pain sensitivity, as measured by the Pain Sensitivity Questionnaire (PSQ), and postoperative pain after TKA.MethodsThe baseline questionnaires, PSQ and Brief Pain Inventory, were given to the patients for self-administration at the presur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
(35 reference statements)
0
19
2
Order By: Relevance
“…Interestingly, a growing body of evidence points to the fact that pain intensity ratings of daily life situations, measured by the PSQ, may be of clinical value. 19 , 20 In contrast to the PSQ, which consists of 17 items, the multiple correlations found in the current study show that even a single concrete question could potentially be used to evaluate sensitivity to pain, at least in an experimental context. The relevance of this finding to clinical pain is yet to be determined.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Interestingly, a growing body of evidence points to the fact that pain intensity ratings of daily life situations, measured by the PSQ, may be of clinical value. 19 , 20 In contrast to the PSQ, which consists of 17 items, the multiple correlations found in the current study show that even a single concrete question could potentially be used to evaluate sensitivity to pain, at least in an experimental context. The relevance of this finding to clinical pain is yet to be determined.…”
Section: Discussionmentioning
confidence: 63%
“…The Pain Sensitivity Questionnaire (PSQ), a self-rating instrument based on pain intensity ratings of 17 daily life situations, showed significant associations with both experimental pain measures in healthy subjects 17 and with postoperative pain intensity in patients. 18 20 Despite that, the clinical applicability of this 17-item questionnaire in the daily busy clinics is challenging, thereby leaving the question of its practical utility open.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In addition, the PSQ scores predicted functional outcome 2 years after lumbar disc herniation surgery. 25 In contrast, Valeberg et al 26 observed that lower scores on one of the PSQ’s subscales were associated with postoperative pain intensity in responders younger than 70 years 8 weeks after total knee arthroplasty.…”
Section: Introductionmentioning
confidence: 95%
“…We chose to use the acute pain episode as an anchoring technique based on an earlier study which showed that the reported intensity of pain of a concrete acute pain episode, even if hypothetical, correlates with actual reports of experimental pain . Moreover, the Pain Sensitivity Questionnaire, which is a self‐rating instrument based on pain intensity ratings of 17 daily life situations, showed significant associations with both experimental pain measures in healthy subjects and clinical pain in patients . The fact that patients in both groups rated the intensity of the painful event equally supports the rationale of using this method as a trustworthy anchoring technique.…”
Section: Discussionmentioning
confidence: 99%